DESIGN OF PLASTIC SHREDDING MACHINE WITH HSS CRUSHER TYPE - Susilawati, Susilawati; Nugraha, Aditya; Buchori, Azhis Sholeh; Rachelia, Faadiyah Cheryl; Pramudia, Mochammad Resa (Department of Mechanical Engineering Education, 2024)
Human commonly use plastic because it is easy to get, economical, heat-resistant, and lightweight. PET plastic is widely used for single-use bottles. This high usage of plastic leads to the accumulation of plastic waste which is difficult to decompose and damaging the environment. The solution is to recycle plastic using an HSS crusher-type plastic shredder. The design process of the HSS crusher-type plastic crusher machine includes: the data collection process, the design starting from the design concept, design embodiment, and design details using Solidworks 2021 Software in two- and three-dimensional forms then processed for design validation. Then, the supervision of the tool manufacturing was continued to determine the suitability of the tool with the created design, machine testing, and evaluation. The dimension of this HSS crusher-type plastic shredding machine design is 775 í— 635 í— 1553 mm with a machine weight of 200 kg. The machine components consist of AS blade, US blade, side blade lock, side blade, UCP 208, size sieve, US knife holder, machine frame, output, holder, US cover, top cover, pulley cover, pulley, output cover, input, hopper, and machine wheel. The engine frame is made by using UNP 50-60 iron. The engine drive is a a 1HP electric motor. The machine made by mild steel plate material which has 10 pcs of steel blades consisting of 6 pcs of steel blades and 4 pcs of sitting blades. The product from this shredded machine is in the form of PET plastic flakes which can be recycled further.